2022
DOI: 10.52662/jksfn.2022.00150
|View full text |Cite
|
Sign up to set email alerts
|

Recent update on trigeminal neuralgia

Abstract: Trigeminal neuralgia (TN), a long-term disorder affecting the trigeminal nerve, is a form of debilitating neuropathic pain. Although the underlying pathogenesis of TN is debatable, loss of myelin along the trigeminal nerve due to direct compression from a blood vessel or secondary to other conditions such as multiple sclerosis or stroke is thought to be the principal cause. Paroxysmal sporadic pain, with unilateral onset, is the main phenomenon of TN. TN is typically diagnosed clinically. Medications, surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…There are also three types of TN: essential, idiopathic, and classical. Blood vessels compressing the trigeminal nerve root as it enters the brain stem is the cause of nearly all occurrences of trigeminal neuralgia ( 2 ). It has been demonstrated that not all patients with TN had vascular compression, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also three types of TN: essential, idiopathic, and classical. Blood vessels compressing the trigeminal nerve root as it enters the brain stem is the cause of nearly all occurrences of trigeminal neuralgia ( 2 ). It has been demonstrated that not all patients with TN had vascular compression, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that not all patients with TN had vascular compression, and vice versa. Although neurovascular compression accounts for most TN cases, primary demyelination disorders, such as multiple sclerosis (MS), can also lead to TN symptoms (2)(3)(4). It is often known that women have trigeminal neuralgia at higher rates than men do (5).…”
Section: Introductionmentioning
confidence: 99%